Emerging research practice for impact in the CGIAR: The case of Index-Based Livestock Insurance (IBLI) - Banerjee, Rupsha R.; Hall, Andrew; Mude, Andrew G.; Wandera, Brenda; Kelly, Jennifer (SAGE Publications, 2019)
Under increased scrutiny by its funders, the CGIAR continues to search for ways of translating research excellence into innovation and developmental impact. Several approaches have been suggested that recognize the interactive nature of innovation. While these have been deemed useful, it is the deeper institutional change agenda that has been a bottleneck in the evolving ways of the CGIAR deploying science for impact. This article documents an example in the CGIAR where significant innovation appears to have taken place in research practice, and where the institutional setting of both the CGIAR center involved and its donors have adapted to accommodate this new approach. The case study presented is recent experiences at the International Livestock Research Institute (ILRI) of developing and facilitating the adoption of Index-Based Livestock Insurance (IBLI) in Kenya and Ethiopia. The approach of the IBLI program evolved as a form of research practice that expands the boundaries of legitimate research practices in the CGIAR: it maintained the essentials of international public goods, but also included activities engaging with innovation processes that led to tangible household impacts. While the development and use of this approach was not without its tensions both within ILRI and with donors funding the work, the approach proved highly successful and won acceptance and legitimacy. This suggests that organizations should encourage and support individual projects and teams to adapt, develop, and adopt different approaches in order to achieve impact. Accepting pluralistic narrative of success will be a critical part of this.